Senegal Climate Risk Management for Agriculture Curriculum Design Workshop - List, Geneva; Trzaska, Sylwia; Braun, Melody; Hansen, James; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project aims to benefit millions of smallholder farmers in Senegal and five other target countries through climate information services and climate smart agriculture. Strengthening the capacity of next users, particularly agricultural extension and advisory service (EAS) providers who work to support farmers in Senegal and five other target countries, is crucial to achieving this goal. Therefore, AICCRA gathered the key EAS partners and stakeholders in a 5-day workshop, held in Dakar, 5-9 December 2022, to: • design a curriculum to strengthen the capacity of EAS providers to incorporate climate services in their work with Senegal’s farmers and agropastoralists, and • formulate a roadmap for implementing the curriculum.